Effect of gender on the etiology of fecal incontinence: Retrospective analysis of a tertiary referral center in Turkey - ATUĞ, ÖZLEN; TOKAY TARHAN, SENA (AVES, 2019)
Background/Aims: Anorectal diseases, including fecal incontinence, are prevalent and have an enormous impact on the quality of life. Therefore, investigating their etiological factors may help to reduce the incidence and/or the severity of the underlying diseases. Materials and Methods: Referral complaints (constipation, strained defecation, and incontinence) and medical and anorectal manometry records of 883 (562 female/321 male, ages 45.17 +/- 1.00 and 48.41 +/- 0.63 years, respectively) patients were evaluated retrospectively. Maximal resting pressure (MRP) and maximal squeeze pressure (MSP) measured by stationary pull-through technique, volume of rectoanal inhibitory reflex, and sensory threshold to rectal balloon distention (ST) were obtained by water perfusion system. Data were compared according to referral complaints, age, gender, parity, and underlying diseases. Results: Incontinence was the most frequent referral complaint in 61.2% of females and 67.6% of males. MRP and MSP were significantly lower in incontinent females than in the other groups. In incontinent males, MSP was lower than the strained defecation group, and ST was higher than the constipation group. Age was negatively correlated with MRP for both of the genders and in all groups. Obstetric trauma (85%) and number of parity (3.40 +/- 2.59) were significantly higher in incontinent females. Moreover, the most prevalent underlying disease was diabetes in incontinent females (13.7%) and neurological diseases, including traumas, in incontinent males (41.5%). Conclusion: Increasing awareness of labor safety, controlling diabetes mellitus, and preventing obstetric traumas may reduce the prevalence of fecal incontinence.
Keywords: Anorectal manometry; fecal incontinence; constipation; gender; RESOLUTION ANORECTAL MANOMETRY; SPHINCTER FUNCTION; NORMAL VALUES; AGE; PREVALENCE; DISORDERS; SEX; PATHOPHYSIOLOGY; SENSATION; IMPACT